REVIVING THE PASSION OF LIFE THROUGH SUICIDE OF VERONIKA’S CHARACTER IN PAULO COELHO’S VERONIKA DECIDES TO DIE (Universitas Islam Negeri Sunan Ampel Surabaya, 2015)
This article deals with psychological approach which concerns the analysis of reviving the passion of life through suicide of Veronika’s character in Paulo Coelho’s Veronika Decides to Die. The study elaborates Alfred Adler’s individual psychology to analyze the process of reviving life’s passion happened in Veronika’s character. In addition, the formalist criticism involves in this thesis with some limitation to describe the Veronika’s character and to analyze her experiences in dealing with the suicide. The study aims to find out that the passion of life can be revived through the attempt of suicide. The method used in this thesis is qualitative, which is used by making the descriptive analysis through the actions and events that related to the identification process of reviving life’s passion done by Veronika in the novel. The study finds that there is an ability to revive the passion of life through the failure suicide in Veronika. The peoples’ innate for striving is driven Veronika to overcome her inferiority feelings. Moreover, the social interest influences Veronika to create the power of herself, so that can change her style of life in order to perceive the goals of life.